2019
DOI: 10.1002/eap.1915
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally derived nitrogen critical loads for northern Great Plains vegetation

Abstract: The critical load concept facilitates communication between scientists and policy makers and land managers by translating the complex effects of air pollution on ecosystems into unambiguous numbers that can be used to inform air quality targets. Anthropogenic atmospheric nitrogen (N) deposition adversely affects a variety of ecosystems, but the information used to derive critical loads for North American ecosystems is sparse and often based on experiments investigating N loads substantially higher than current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…We used potable local water (McDonald Farms Enterprises, Frederick, CO) that met US EPA drinking water standards. Therefore, added water was not a significant source of nitrogen relative to typical annual atmospheric inputs (Burke et al, 2002, 2008) and well below nitrogen critical load estimates for regional grasslands (Symstad et al, 2019).…”
Section: Methodsmentioning
confidence: 82%
“…We used potable local water (McDonald Farms Enterprises, Frederick, CO) that met US EPA drinking water standards. Therefore, added water was not a significant source of nitrogen relative to typical annual atmospheric inputs (Burke et al, 2002, 2008) and well below nitrogen critical load estimates for regional grasslands (Symstad et al, 2019).…”
Section: Methodsmentioning
confidence: 82%
“…Water was applied using a hand‐held watering wand attached to a flow meter and pump to deliver potable water from a local water delivery service (McDonald Farms Enterprises). Added water met US EPA drinking water standards and thus was not a significant source of nitrogen compared to annual atmospheric inputs (Burke et al., 2002, 2008) and was well below nitrogen critical load estimates for regional grasslands (Symstad, Smith, Newton, & Knapp, 2019).…”
Section: Methodsmentioning
confidence: 88%
“…Added water met US EPA drinking water standards and thus was not a significant source of nitrogen compared to annual atmospheric inputs (Burke et al, 2002(Burke et al, , 2008 and was well below nitrogen critical load estimates for regional grasslands (Symstad, Smith, Newton, & Knapp, 2019).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 96%
“…Invasive species may be better adapted than native species to take advantage of these supplements ( Dukes and Mooney 1999 ). A CO 2 enrichment experiment in a greenhouse showed that five species of invasive plants in the Great Plains followed this pattern ( Ziska 2003 ), and a field experiment in northern mixed-grass prairie suggests that cheatgrass and field brome respond positively to levels of nitrogen enrichment expected from atmospheric deposition ( Symstad et al 2019 ). A special report of IPCC (Intergovernmental Panel on Climate Change) working group for North America highlighted the facilitative effect of elevated CO 2 and regional climate change on the invasion of woody C 3 species into C 4 grasslands ( Watson et al 1998 ).…”
Section: Climate Changementioning
confidence: 99%